2020
DOI: 10.14689/ejer.2020.89.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Servant Leadership and Organizational Citizenship Behavior with Mediation of Psychological Empowerment

Abstract: The purpose was to investigate the relationship between servant leadership and teachers' organizational citizenship behavior with mediating role of psychological empowerment.Research Methods: This study was an applied and correlation research method based on structural equation modeling. 281 teachers of Zahedan city were studied by stratified random sampling method. To collect information, three questionnaires were used: servant leadership (Gholipur et al., 2009), organizational citizenship behavior (Podsakoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The findings revealed a significant and positive relationship between servant leadership and teacher OCB. The finding of this study is expected to be in line with those of previous studies such as (Ghalavi & Nastiezaie, 2020;Kumar et al, 2022;Rosnani, 2018;Van der Hoven et al, 2021;Wulandari et al, 2021). At the school level, teachers are more likely to collaborate with principals who care about their personal development and treat them with a positive and humble attitude.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings revealed a significant and positive relationship between servant leadership and teacher OCB. The finding of this study is expected to be in line with those of previous studies such as (Ghalavi & Nastiezaie, 2020;Kumar et al, 2022;Rosnani, 2018;Van der Hoven et al, 2021;Wulandari et al, 2021). At the school level, teachers are more likely to collaborate with principals who care about their personal development and treat them with a positive and humble attitude.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has shown that servant leaders can significantly influence the work behaviour of secondary high school teachers in Zahedan city to go above and beyond their essential duties by exhibiting OCB (Ghalavi & Nastiezaie, 2020). Another study in the Western Cape Province of South Africa found a positive relationship between servant leadership, psychological empowerment, and teacher OCB ( Van der Hoven et al, 2021).…”
Section: Literature Review Servant Leadershipmentioning
confidence: 99%
“…In studies of Nobari et al. (2014), Faruqi and Hafidz (2019) and Ghalavi and Nastiezaie (2020), the authors recorded an indirect significant link between servant leadership and OCB.…”
Section: Introductionmentioning
confidence: 91%
“…Empowerment is not an easy process to implement it requires teamwork to succeed (Çakar & Ertürk, 2010). Organisational culture improves how employees perform which ultimately improves the organisation's performance, this can only be achieved if the environment is transformed from a command and control to a more supportive and empowering environment (Ghalavi & Naser, 2020).…”
Section: Empowerment As An Aspect Of Organisational Culturementioning
confidence: 99%
“…The theory on psychological empowerment explains; "that the work environment leads to the development of an active motivational orientation, which in turn leads to proactivity and organizational citizenship behavior" (Kang, et al, 2017, p. 178). Employing useful and productive strategies enhances the empowerment process (Ghalavi & Naser, 2020). Psychological empowerment has been described as an, "intrinsic task motivation reflecting a sense of self-control in relation to one's work and an active involvement with one's work role" (Seibert, et al, 2011, p. 981).…”
Section: Psychological Empowermentmentioning
confidence: 99%